2015
DOI: 10.1007/s10452-015-9540-5
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macro-invertebrate fauna associated with Dreissena mussels in the Meuse River: from incapacitating relationships to facilitation

Abstract: Dreissena (Bivalvia: Dreissenidae) species can act as ecosystem engineers, physically altering freshwater ecosystems and changing benthic macroinvertebrate assemblages. The mussel beds they form can provide shelter and food for detritivorous species, whereas fouling can directly impact native bivalves. In this study, we examined the effects of the zebra mussel (Dreissena polymorpha) and quagga mussel (Dreissena rostriformis) on the macro-invertebrate community in the Meuse River by characterizing the macro-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…However, the taxonomical revision performed by [79] and the analyses based on mitochondrial genomes performed by [80] revealed genetic distinctions among these taxa. Furthermore, a COI gene analysis performed on Chelicorophium revealed that the specimens clustered in two separate groups corresponding to C. curvispinum and to C. robustum [81], which is consistent with our data obtained in the case of the Lower Danube specimens.…”
Section: Discussionsupporting
confidence: 91%
“…However, the taxonomical revision performed by [79] and the analyses based on mitochondrial genomes performed by [80] revealed genetic distinctions among these taxa. Furthermore, a COI gene analysis performed on Chelicorophium revealed that the specimens clustered in two separate groups corresponding to C. curvispinum and to C. robustum [81], which is consistent with our data obtained in the case of the Lower Danube specimens.…”
Section: Discussionsupporting
confidence: 91%
“…In Poland, S. woodiana has been known since the 1980s only from artificially heated areas (Kraszewski, 2007) until recently, when it started to appear in natural waters (Cichy et al, 2016), including our study site. Similarly, American unionids, having no contact with dreissenids until the 1980s, seem to be more affected by biofouling (Ricciardi, 2003;Ricciardi et al, 1996;Strayer & Malcom, 2007) than European species (Burlakova et al, 2000;Lewandowski, 1976;Marescaux et al, 2016). Thus, that is why S. woodiana could be more sensitive to zebra mussel fouling.…”
Section: Consequences Of Mussel Fouling To Unionidsmentioning
confidence: 99%
“…This typically happens when introduced taxa occupy a new biotope and out‐compete their trophic competitors (Ward & Ricciardi, ). This is the case in freshwater systems where exotic Dreissenidae mussels ( Dreissena polymorpha and Dreissena bugensis ) or Corbiculidae have been shown to reduce populations of other large filter‐feeding taxa such as Sphaeriidae and Unionidae (Marescaux et al., ). However, if food is abundant, two species could share the same resources without negatively impacting each other (Pianka, ).…”
Section: Introductionmentioning
confidence: 99%